The effect of climate change on the precipitable water content in the north coast of the Persian Gulf - Tayebeh Dehghani; mohammad saligheh; Bohloul Alijani (تحقیقات کاربردی علوم جغرافیایی)
In order to detect climate change, a variety of climate indicators can be used which is often considered temperature and precipitation. In order to investigate the effect of climate change on the amount of precipitation in the north coast of the Persian Gulf, it simulated the precipitable water for 2017-2050 based on the RCP4.5 model of the Hadcm3 model. The NCEP / NCAR base-station data with an arc-value of 0.125 was used to analyze the past and present precipitable water patterns and to reveal the process of this time series. Time series analysis of precipitable water was performed using two SENS tilt estimators and Man-Kendall test. The results indicated that the annual time series of rain water was increasing in the region, every year, 0.05 mm, the precipitated water increased and it tended to become more homogeneous, this increase in the significance level of 0.95. The precipitation rate in the eastern part of the region was higher than other areas. Before 1989, several fluctuations were observed in the rainy season of precipitable water, but none was statistically significant at the confidence level of 95%, but since 1989, the trend has increased significantly at a confidence level of 0.95. This spatial behavior of precipitable water can actually have occurred in response to the increase in the overall temperature of the area and can be considered as a profile of climate change in the region.